Barriers to specialist palliative care in interstitial lung disease: a systematic review. Issue 2 (21st November 2018) - Kim, Jee Whang; Atkins, Chris; Wilson, Andrew M
Abstract : Background: Current guidelines recommend palliative care based on individual needs for patients with idiopathic pulmonary fibrosis. However, patients with interstitial lung disease (ILD) are less likely to receive specialist palliative care services compared with patients with malignant disease. The aim of this review is to summarise recent studies addressing barriers to referring patients to specialist palliative care services. Methods: PubMed, Embase, Medline and Web of Science were reviewed to identify relevant publications. Studies were selected if they examined the frequency of specialist palliative care referral and/or addressed issues surrounding access to palliative care services for patients with ILD. Results: Ten studies with a total of 4073 people with ILD, 27 caregivers and 18 healthcare professionals were selected and analysed. Frequency of palliative care referrals ranged from 0% to 38%. Delay in palliative care referrals and end-of-life decisions, patients' fear of talking about the future, prognostic uncertainty and confusion about the roles of palliative care were identified as barriers to accessing palliative care services. Conclusion: Further research should concentrate on the early identification of patients who need specialist palliative care possibly with establishment of criteria to trigger referral ensuring that referrals are also based on patient's needs.